Reinforcing effect of imidazole modified nanosilica on thermal and mechanical properties of anhydride based epoxy system. (2020) - Prasad, Tankeshwar; Halder, Sudipta; Dhar, S.S.
Abstract: In this study, imidazole modified nanosilica (IS) was prepared from TEOS precursor by sol-gel via co-condensation method. The surface modification was confirmed by FTIR and SEM characterization. Further, epoxy nanocomposites were prepared using different content (0-3 wt %) of IS. TGA analysis demonstrated the significant effect of IS towards enhancement of thermal stability of epoxy composites at 1 wt% IS particle contents. The maximum enhancement in tensile strength of composites (1 wt% IS) was achieved by 45% with respect to neat epoxy. From these results, it confirms that the organic compatibility and chemical bonding at the interface around IS favours effective stress transfer to the matrix system. Thus, this work exposed the potential of imidazole modified nanosilica as a good choice of reinforcement in the field of composite industries.